Delayed Cooling or Suboptimal Storage Temperatures Reduce Butterhead Lettuce Shelf-Life - Agüero, Maria Victoria (2014)
Crated or uncrated butterhead lettuce (Lactuca sativa L.) var. Lores responds to environmental conditions during early postharvest, the first 24 h after harvest. The present work examines the effects of environmental conditions during early postharvest on quality indices in refrigerated storage. Additionally, effects on shelf-life were estimated using the modified Global Stability Index methodology. Quality indices at the start of storage were higher for heads exposed to optimal conditions immediately after harvest than for heads exposed to suboptimal ones. Despite these initial differences, changes in almost all quality indices were independent of storage condition. Similar responses were found for water content, bound and free water, ascorbic acid, total chlorophyll, and overall visual quality. Changes in relative water content and mesophilic bacteria counts during refrigerated storage were a function of environmental condition during the first 24 h after harvest. Maintenance of optimal environmental conditions during the first hours after harvest prolonged shelf-life to 12 days compared to heads exposed to suboptimal conditions during the early postharvest period. These results impact marketing of the produce and support the idea that proper handling during early postharvest diminishes quality loss and prolongs shelf-life, allowing butterhead lettuce to reach more distant markets. © 2014 Copyright Taylor and Francis Group, LLC.